2014
DOI: 10.1093/rheumatology/keu041
|View full text |Cite
|
Sign up to set email alerts
|

Safety of resuming tumour necrosis factor inhibitors in patients who developed tuberculosis as a complication of previous TNF inhibitors

Abstract: Our results suggest that resuming TNFi therapy in patients following adequate TB treatment is safe, even before completion of TB treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…There is no consensus on when TNF-α inhibitor therapy can be resumed. However, small case series suggest that it is safe to resume TNF-α inhibitor therapy in patients who complete at least 2 months of antituberculosis treatment and have a good clinical response [380,386,387]. The decision to restart TNF-α inhibitor treatment should be individualized, taking into account the clinical need for immunosuppressive therapy, the extent of tuberculosis disease, and clinical response to antituberculosis treatment.…”
Section: Other Comorbid Conditionsmentioning
confidence: 99%
“…There is no consensus on when TNF-α inhibitor therapy can be resumed. However, small case series suggest that it is safe to resume TNF-α inhibitor therapy in patients who complete at least 2 months of antituberculosis treatment and have a good clinical response [380,386,387]. The decision to restart TNF-α inhibitor treatment should be individualized, taking into account the clinical need for immunosuppressive therapy, the extent of tuberculosis disease, and clinical response to antituberculosis treatment.…”
Section: Other Comorbid Conditionsmentioning
confidence: 99%
“…There is no guideline available for when or how to restart anti-TNF-α agents for uveitis during or after treatment of active TB. In other fields of medicine where biologics are used, few retrospective studies have found that restarting of the same anti-TNF-α agents and other biological agents, even during ATT appears to be safe 18 19. Furthermore, there is increasing evidence in the literature to support that life-threatening infection may, in fact, prevent autoimmune response by apoptotic depletion of naïve T-cells 20…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al. showed that resuming TNFα inhibitors was safe in patients who received anti-TB treatment [12]; however, the optimal time for restarting anti-TNFα treatment has not yet been determined. Our case demonstrated that a flare of circulating TNFα could occur shortly after initiation of anti-TB therapy and discontinuation of TNFα-blocking agents.…”
Section: Discussionmentioning
confidence: 99%